Perancangan Aplikasi Sistem Informasi Administrasi pada Toko Gloria Comp dengan Metode FIFO - Rendy Hardiawan; Djoni Haryadi Setiabudi (Jurnal Infra, 2017)
Effectivity and efeciency is one of the most needed factory by human, it is because of their growing activity to do their business. This is surely increase the human needs of more effective and efficient technology. There are so many business that have already harness the technology advances, it can be clarified from the business transaction that arecomputerised. Because technology usage can help business to work effectively and effecintly. From the background above Gloria Comp Shop tried to improve ther effectiveness and effciency from their business process by making a web application. Hopefully, this website could ease the administration process that are happening in Gloria Comp Shop. All the feature such as purchase, sale, and report can be accessed from one system so it will decrease the human error risk. From the conducted research, administration web application built already fulfill the basic needs of the user. User canfeel the effectiveness and afficiency in the Gloria Comp Shop administration data processing process.